Lower Lid Entropion in a 78-year-old Female: A Case Repor (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2022)
Introduction: Entropion is a malposition of the eyelids in which the eyelid margin folds inward and causes irritation to the eye. It can be caused by congenital, spastic, cicatricial and involutional entropion. Involutional entropion affects 10.6% in group over the age of 60, especially in Asian races as compared to Caucasian races.1 It can have adverse effect on the eye such as trichiasis in which the eyelashes protrudes inwards towards the eyeball, leading to persistent erosions of punctate epithelium, pannus formation or ulcers. Definitive treatment for entropion is surgical intervention when feasible, such as the Jones procedure. The prognosis of corrective surgical intervention is highly correlated to the successfulness of the surgery and wound healing process of the patient, thus needing highly accurate and cautious procedure.2 Methods: This case report was taken from the Eye Clinic of Rumah Sakit Umum Siloam, in February 2022. Results: A 78 years-old female presented with complaints of discomfort, foreign body sensation, irritation, itching, and glare in both eyes since 1 year ago. She had a history of cataract surgery 3 years ago. Conclusions: Anamnesis and ophthalmological examinations results lead to suspected glaucoma, involution entropion ODS and pseudophakia ODS. Blepharoplasty was performed on the patient with appropriate surgical and therapeutic techniques. The post-operative examination showed results indicating a good prognosis in this patient.